Microwave‐assisted aqueous synthesis of new quaternary‐alloyed CdSeTeS quantum dots; and their bioapplications in targeted imaging of cancer cells. (14th June 2012) - Yang, Fengzhao; Xu, Zhancheng; Wang, Jinjie; Zan, Feng; Dong, Chaoqing; Ren, Jicun
ABSTRACT: In this study, we report for the first time a one‐pot approach for the synthesis of new CdSeTeS quaternary‐alloyed quantum dots (QDs) in aqueous phase by microwave irradiation. CdCl2 was used as a Cd precursor during synthesis, NaHTe and NaHSe were used as Te and Se precursors and mercaptopropionic acid (MPA) was used as a stabilizer and source of sulfur. A series of quaternary‐alloyed QDs of different sizes were prepared. CdSeTeS QDs exhibited a wide emission range from 549 to 709 nm and high quantum yield (QY) up to 57.7 %. Most importantly, the quaternary‐alloyed QDs possessed significantly long fluorescence lifetimes > 100 ns as well as excellent photostability. Results of high‐resolution transmission electron microscopy (HRTEM), energy dispersive X‐ray spectroscopy (EDX) and powder X‐ray diffraction (XRD) spectroscopy showed that the nanocrystals possessed a quaternary alloy structure with good crystallinity. Fluorescence correlation spectroscopy (FCS) showed that QDs possessed good water solubility and monodispersity in aqueous solution. Furthermore, CdSeTeS QDs were modified with alpha‐thio‐omega‐carboxy poly(ethylene glycol) (HS‐PEG‐COOH) and the modified QDs were linked to anti‐epidermal growth factor receptor (EGFR) antibodies. QDs with the EGFR antibodies as labeling probes were successfully applied to targeted imaging for EGFR on the surface of SiHa cervical cancer cells. We believe that CdSeTeS QDs can become useful probes for in vivo targeted imaging and clinical diagnosis. Copyright © 2012 John Wiley & Sons, Ltd.